Precision intervention of virtual reality training for balance and gait in Parkinson’s disease: a dose–response meta-analysis - Wu, Hailong; Zhang, Cheng (Frontiers in Neurology, 2025)
BackgroundThis study systematically evaluated the effects of virtual reality training (VRT) on balance ability and functional gait in Parkinson’s disease (PD) patients and used dose–response analysis to quantify optimal intervention parameters, providing evidence-based guidance for clinical rehabilitation.MethodologyThis systematic review and meta-analysis followed PRISMA guidelines and was registered with PROSPERO (CRD420251008459). Six databases, including PubMed, Embase, and Cochrane Library, were searched for RCTs published before March 15th, 2025. Studies were included if they involved PD patients, used VRT, and reported BBS or 6MWT data. A random-effects model was used for meta-analysis to assess VRT’s effects and explore optimal training parameters through dose–response analysis.ResultsThirty-two RCTs involving 547 participants were included. VRT significantly improved balance function (BBS: WMD = 3.63, 95%CI 2.89–4.37, p < 0.01) but did not significantly improve 6MWT (WMD = 17.64 m, 95%CI 5.3–40.6, p = 0.13). Dose–response analysis indicated optimal parameters for BBS improvement: single session 0–20 min, weekly training volume 201–300 min, frequency 4–7 times/week, total duration 4–7 weeks, and total sessions >40. For 6MWT optimization, parameters were single session 21–40 min, frequency 4–7 times/week, and total duration 4–7 weeks.ConclusionVRT significantly improves balance function in PD patients, with a recommended dose of ≤20 min per session, 4–7 times weekly for 4–7 weeks (>40 total sessions). Though not statistically significant for functional gait, the effect size reached MDIC, particularly in non-Asian regions, where sessions of 21–40 min for 4–7 weeks are suggested. Key findings include regional differences, dose specificity, and technical versatility.